Small bowel obstruction by a giant fecal bezoar in a blind loop of small intestine: a case report - Chen, Ziwen; Wu, Youbo; Xi, Kexing (Frontiers in Medicine, 2025)
Blind loop syndrome (BLS) is a clinical condition characterized by bacterial overgrowth and stasis within intestinal blind loops, which may result from anatomical abnormalities such as diverticula, fistulae, or surgical anastomoses. While end-to-side and side-to-side intestinal anastomoses are common surgical techniques, the latter has been associated with a higher risk of BLS due to the potential formation of stagnant segments. This case report presents a rare instance of small intestinal obstruction caused by large fecalith formation within a blind loop 1 year after side-to-side anastomosis. The clinical presentation, diagnostic approach, and management strategies are discussed in detail. This report highlights the importance of surgical technique selection and standardization in preventing BLS-related complications, providing valuable insights for clinical practice.